PENGARUH PROFITABILITAS, SOLVABILITAS, UKURAN PERUSAHAAN, OPINI AUDIT DAN UKURAN KANTOR AKUNTAN PUBLIK TERHADAP AUDIT DELAY (Kajian pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2019) - Tri Widyastuti; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2022)
This study aims to examine and obtain empirical evidence about the effect of profitability, solvency, company size, audit opinion, and public accounting firm size on Audit Delay. The independent variables in this study are Profitability, Solvency, Company Size, Audit Opinion, and Public Accounting Firm Size, and the dependent variable used in this study is Audit Delay.This study used secondary data. They used are sourced from the financial statements of companies listed on the IDX and published by the IDX on the website www.IDX.co.id. This research used the purposive sampling technique. The number of samples is 164 companies consistently listed on the IDX in the 2016-2019 period. This research used a t-test, F test, and coefficient of determination.The results showed that during the observation period, Profitability, Audit Opinion, and The Public Accounting Firm Size have a significant adverse effect on the Audit Delay, while solvency as proxied by Debt to Total Assets Ratio and Company Size has no significant effect. This result means that companies that experience good news (profitable and get an Audit-unqualified opinion) faster publish their financial statements. Likewise, the Big Four's Public Accounting Firm Size is relatively shorter than the others of an audit delay period.